The Social Impact of Charles Dickens in the Victorian Era: A Socio-Literary Analysis through Foucault and Goldmann - Prasasti, Siska; Widyatwati, Ken; Suryadi, M. (Journal of Language and Literature Studies, 2025)
This research examines the influence of Charles Dickens’s literary works in criticizing the social, political, and economic conditions of Victorian Britain, particularly through the lens of social criticism. This research is based on the idea that literature, especially novels, can serve as a powerful medium for social criticism and reform. Using a qualitative descriptive method, the research analyzes selected novels: Oliver Twist, Hard Times, Bleak House, Great Expectations, and A Christmas Carol to identify dominant social themes such as poverty, child exploitation, institutional injustice, and class disparity. These themes are interpreted using Michel Foucault’s theory of disciplinary power and the author function, along with Lucien Goldmann’s concept of collective consciousness. The results of this research show that Dickens’s narratives not only portrayed systemic oppression but also influenced public opinion by exposing the failures of modern institutions and evoking empathy across class lines. For example, Oliver Twist critiqued the Poor Law system, which contributed to shifting public perception and inspired social reforms in child welfare. Dickens’s works served as cultural interventions that shaped moral discourse and supported progressive change. This research concludes that Charles Dickens is not only a great writer but also a social reformer whose works contributed significantly to societal change. This research highlights the literature’s potential to raise awareness of injustice and serve as a catalyst for broad social impact. Future research may explore similar ideological frameworks in other Victorian authors or analyze Dickens’s impact on modern social thought.